J-aggregates - Kobayashi, T. (Takayoshi) (World Scientific, 1996)
J-aggregates have a long history of research but so far no books have been published on this group of very interesting materials. The book is on the structures, electronic states, linear and nonlinear optical properties and spectroscopies of the J-aggregates. Various properties and processes of J-aggregates such as superradiance, excitons, photon echo, geometrical structure, electron transfer and femtosecond spectroscopy are also discussed. The contributors are those actively working in the field.